Faktor-Faktor yang Berhubungan Dengan Kejadian Malaria Di Wilayah Pertambangan Emas tanpa Izin (PETI) Kecamatan Mandor Kabupaten Landak Propinsi Kalimantan Barat - Salim, Maulidiyah; Suhartono, Suhartono; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Malaria disease is one of many health problems in Indonesia. The National Annual Parasite Incidence (API) in 2009 is 1.85 per 1,000 people with the provincial range of 0.02 – 27.66 per 1.000 people. According to the data of Health Profile in West Kalimantan in 2009, the clinical malaria was 55.987 and positive malaria was 17.885.In Landak County in 2009, the number of clinical malaria was 4.656 and positive malaria was 698.Methode : This research was an observasional reserved with the approact case control. The case was the in habitants malaria in the period January to December 2011 and the control was the in habitants who free from have malaria.The number of the respondents was 132 samples. Data collection was conducted by interviews and environmentalobservation. The statistical analysis used univariate analysis, bivariate analysis, and simple regression multivariate analysis; and the instrument used to calculate the amount of risk was the odd ratio (OR).Result : The factors that were proven to correlate to the cases of malaria disease were the finding of Anopheles sp.larva in the water of lagoon and swamp, the existence of the lagoon (p = 0.037; OR = 2.414; CI 95 95% = 1.118 –5.211), the usage of mesh on the house ventilations (p = 0.034; OR = 5.714; CI 95 95% = 1.201 – 7.192), the habit of using mosquito net (p = 0.004; OR = 5.378; CI 95 95% = 1.700 – 7.014), the habit of using mosquito repellent (p = 0.000; OR = 6.5; CI 95 95% = 2.935 – 4.394), and the habit of going out of the house at night (p = 0.006; OR = 7.849; CI 95 95% = 1.695 – 6.341).From the multivariate analysis by binary logisticregression, the risk factors influencing on the malaria cases were found: the use of mosquito net, the use of mesh on the house ventilations, the use of mosquito repellent, and the habit of going out of the house at night. The most dominant factor was the use of mosquito repellent with p = and CI 95% = 3.048 – 18.033. Based on the analysis results, it can be found that the use of mosquito net, the use of mesh on the house ventilations, the use of mosquito repellent, and the habit of going out of the house at night have the probability of the risk of having malaria is as much as 95.5%.Keywords : endemic area, malaria, risk factors, area of gold mining